PENGARUH KUALITAS PELAYANAN DAN STRATEGI HARGA TERHADAP KEPUASAN PENUMPANG JASA ANGKUTAN UMUM TRAYEK 120 PADA PT. RAHAYU MEDAN CERIA MEDAN - Novien Rialdy (Universitas Medan Area, 2017)
Each firm transportation service providers must act quickly and precisely as a consequence of the internal and external environment changes that occur in the orientation to provide the best service to customers. Companies in the operations must always observe the changes in consumer behavior in order to anticipate changes in the behavior, then reduced to the study in order to improve their marketing strategies.The problem of this research is “whether service quality effect on passenger satisfaction of public transport services route 120 at PT. Rahayu Medan Ceria Medan, whether the pricing strategy of passenger satisfaction influence on public transport services route 120 at PT. Rahayu Medan Ceria Medan and whether the quality of service and pricing strategies simultaneously affect the satisfaction of the public passenger transport services on the route 120 PT. Rahayu Medan Ceria Medan.After collecting data on the samples filed, as well as data analysis, it is known that from the research that has been described in previous chapters, it can be concluded that the quality of service and pricing strategy has simultaneous effect on passenger satisfaction public transportation services route 120 at PT. Rahayu Medan Ceria Medan. In other words, the variability of passenger satisfaction which can be explained by using the variable quality of service and pricing strategy. Based on this it can be concluded that the quality of service and pricing strategy implemented in public transport services route 120 at PT. Rahayu Medan Ceria Medan has been running well and is able to give effect to passenger satisfaction. Quality of service has an influence on passenger satisfaction employees of public transport services route 120 at PT. Rahayu Medan Ceria Medan. Keywords: Quality of Service, Pricing Strategies, Passenger Satisfaction